A Suite of Tools for Assessing Thematic Map Accuracy. (11th June 2014) - Mas, Jean-François; Pérez-Vega, Azucena; Ghilardi, Adrián; Martínez, Silvia; Loya-Carrillo, Jaime Octavio; Vega, Ernesto
Abstract : Although land use/cover maps are widely used to support management and environmental policies, only some studies have reported their accuracy using sound and complete assessments. Thematic map accuracy assessment is typically achieved by comparing reference sites labeled with the "ground-truth" category to the ones depicted in the land use/cover map. A variety of sampling designs are used to select these references sites. The estimators for accuracy indices and the variance of these estimators depend on the sampling design. However, the tools used to assess accuracy available in the main program packages compute the accuracy indices without taking into account the sampling and give inconsistent estimates. As an alternative, we present free user-friendly tools that enable users beyond the Geographic Information Science Community to compute accuracy indices and estimate corrected areas of given categories with their respective confidence intervals. The tool runs in Dinamica EGO, a free platform for environmental spatial modeling as well as a Q-GIS plugin and a R package. Additionally, a practical application example is described using a case study area in central-west Mexico.